Different statuses for the sediment process of Cr in Jiaozhou Bay. Issue 4 (February 2019) - Yang, Dongfang; Zhu, Sixi; Wang, Xiaodan; Wang, Ming; Yang, Xiuqin
Abstract: Using investigation data on chromium (Cr) in surface and bottom waters in Jiaozhou Bay in April, July and October 1982, this paper analyzed the sediment processes of Cr. Results showed that the horizontal distributions and vertical variations of Cr in waters were strongly impacted by overland runoff. The sediment process of Cr in Jiaozhou Bay within year could be divided into three statuses. Status 1: little source input from overland runoff. In April the wet season was not coming yet, and the source input of Cr from overland runoff was little, and there was little influence on Cr contents in waters far away from the coast in the southwest, and there was sediment process in coastal waters in the southwest of the bay. Status 2: strong source input from overland runoff. In July the wet season was coming, and the source input of Cr from overland runoff was strong, and there was strong influence on Cr contents in waters near the coast in the southwest, and there was sediment process in waters far away from the coast in the southwest of the bay since the continuous input of Cr from overland runoff. Status 3: the source input from overland runoff was over. In October the wet season was over, and the source input of Cr from overland runoff was weak, and there was little influence on Cr contents in waters, and in the coastal waters in the southwest of the bay the vertical variations were returning to the status before the source input since the continuous sediment of Cr in the past wet season.